Exploring sustainable logistics practices toward a circular economy: A value creation perspective. (14th June 2022) - Jayarathna, Chamari Pamoshika; Agdas, Duzgun; Dawes, Les
Abstract: Transforming toward a circular economy (CE) is a viable strategy for achieving sustainable logistics systems. However, it is still unclear how this transformation should be approached because there is limited knowledge in this context. This study aims to explore how the logistics sector incorporates sustainability practices toward CE. To achieve this aim, we addressed the research questions of (RQ1) what sustainability practices are used by the logistics sector and (RQ2) how these practices contribute to transforming the logistics sector into CE. We used a qualitative approach to address these questions by interviewing 14 logistics service providers. Interview transcripts were analyzed by using coding, categorizing, and finding relationships among the concepts identified from the literature following the Gioia method. We identified 47 sustainable logistics practices under nine categories from three key themes: environmental preservation, firm's dynamic capabilities, and social well‐being. We used the natural resource‐based view, dynamic capabilities, and social well‐being theories to identify the key themes. These theories contributed to the existing knowledge on CE strategies from the aspects of environmental, economic, and social value in transforming the logistics sector into CE. We built three propositions based on the findings and the propositions highlight that economic value creation is the core benefit followed by environmental and social value creation in the CE transformation. The identified three themes will provide a holistic approach for implementing CE within the logistics sector.